Experience using aripiprazole in the complex treatment of PTSD due to the war in Ukraine - Pustovoyt Михайло; Krasnopolska Ірина; Panchyshyn Михайло; Pushko Антоніна; Dzivak Катерина; Romash Іван (Psychosomatic Medicine and General Practice, 2023)
Relevance. Our country has fully experienced the incomprehensibility and fragility of the modern world with the beginning of the anti-terrorist operation in eastern Ukraine, later going through the COVID-19 pandemic with all its devastating consequences, and finally suffering a treacherous attack from a neighboring state that until recently positioned itself as “fraternal”.It is understandable that all of this has significantly influenced the overall anxiety, fear of the future, and lack of trust of the population as a whole, subjecting large segments of the population to an increased risk of developing post-traumatic stress disorder (PTSD) associated with being in a combat zone, among military personnel and war veterans, among forced migrants, and among those who have experienced violence and torture. Obtaining effective treatment is crucial for reducing disorder symptoms and improving functioning. Modern treatment options for PTSD include both psychological and pharmacological interventions. Since we currently have a large influx of patients with post-traumatic stress disorders, both as a result of combat stress and other mass stressors, it is necessary to review approaches to the treatment of such patients and choose the most effective and accessible ones for the majority of specialists. Of course, the effectiveness of trauma-focused psychotherapeutic methods is difficult to overestimate, and most of our professionals have undergone or are undergoing training in their application. However, one should not forget about the vast arsenal of available and effective medications that can effectively prepare a patient for psychotherapeutic treatment or serve as a complement to psychotherapy. Objective. The objective of our study was to investigate the effectiveness of the atypical antipsychotic aripiprazole in the comprehensive treatment of PTSD and its mechanisms of influence on different clusters of PTSD, as well as comorbid disorders. Materials and Methods. A literature analysis was conducted on the effectiveness of various PTSD therapy methods, including chronic complex PTSD and PTSD with comorbid psychiatric disorders and addictions. Our own clinical studies are being carried out on patients with PTSD undergoing inpatient and outpatient treatment at the “Prykarpatskyi Regional Clinical Mental Health Center of the Ivano-Frankivsk Regional Council” and the First Volunteer Surgical Hospital of the “BRASS” clinic. The group primarily consisted of males aged 21 to 45 with PTSD related to military actions and verified according to contemporary diagnostic criteria. Clinical-psychopathological examination and psychodiagnostic methods were used, including the Clinical-Administered PTSD Scale (CAPS) for clinical diagnosis of PTSD, the Hospital Anxiety and Depression Scale (HADS), the Dissociative Experiences Scale (DES), Richard Lazarus’ Psychological Diagnosis of Coping Behavior Strategy, the Quality of Life Assessment Scale (Chaban O.S., 2008), and others. A follow-up method was also employed to assess the results of the comprehensive treatment program. It should be noted that this article serves as a preliminary report, and the statistically analyzed results of the study will be reported in our future publications. Results. Aripiprazole can be considered one of the most promising antipsychotic agents for the treatment of post-traumatic stress disorders in a comprehensive approach alongside psychotherapy, and in certain cases, as monotherapy, considering its broad spectrum of action and minimal side effects. The key to successful treatment is the establishment of trusting and collaborative relationships with the patient when prescribing medication. Psychological preparation of patients regarding side effects, necessary dosages, treatment duration, and compliance can significantly improve outcomes. It is necessary to consider and discuss side effects, as well as weigh the risks and benefits of continued treatment. It is important to discuss treatment response and coordinate efforts. The doctor should engage in an ongoing dialogue with the patient regarding the effects of the medications and the presence of side effects. It is also crucial for the patient to actively participate in the treatment process rather than feeling like a passive recipient of medication to alleviate symptoms. Conclusions. Trauma-focused psychotherapy is certainly the main method for treating PTSD, and in cases of recent uncomplicated PTSD, it may be the sole treatment method. However, considering the fact that we are increasingly encountering complex PTSD with psychotic dissociative symptoms, significant disruptions in the affective domain, and anticipating an increase in such cases in the future, we understand that psychotherapy may be ineffective or entirely unattainable in such situations. Currently, pharmacotherapy for post-traumatic stress disorders primarily focuses on SSRI/H antidepressants, adrenergic blockers, and short courses of benzodiazepines. Previous attempts at antipsychotic pharmacotherapy for post-traumatic stress disorders were mainly focused on the “dones” and “pines” groups, whose side effects (sedation, cardiometabolic effects, dyskinesia) hindered successful treatment. The new generation antipsychotic, “doublepipe-rip” aripiprazole, demonstrates effectiveness in influencing all clusters of PTSD: intrusive, avoidance, hyperarousal, and additionally shows efficacy in treating complex PTSD and comorbid disorders with PTSD, supported by numerous studies and practical experience. It makes sense to take a closer look at the role of antipsychotic medications in the treatment of PTSD, considering the specific characteristics of aripiprazole and possibly other newer antipsychotics, and consider them as effective agents for augmentation, and sometimes even monotherapy, in the treatment of PTSD and complex PTSD.